PERSPECTIVES OF TRANSPORT DIRECTION TASKS APPLICATION IN THE OPTIMIZATION OF MANUFACTURING SCHEME AND SUPPLY OF RAW MATERIALS - Lesnikova, I. Y.; Medvediev, I. P.; Khalipova, N. V.; Kuzmenko, A. I.; Razghonov, S. A. (Systems and Technologies, 2019)
Considered the problem of production processes optimization by applica-tion of transport direction tasks. The development of approaches to improve the existing production process based on the calculation of rolling mill capacity to ensure the production of the required number of kits during the month is ana-lyzed. An optimization problem is investigated in order to minimize the total time for preparatory operations for assembly of metal structures, taking into account the location of the existing transport network of the region.With the help of the maximum flow task determined the possibility of the re-quired production volume delivery from a certain point of manufacture to a spe-cific warehouse in accordance with the existing production schemes of the enter-prise. In the mathematical model to solve this problem, a linear programming problem proposed to find the volume of production when using certain equip-ment; the restriction specifies the possibility of supplying the workpiece of certain products.Using the circular route problem, established a sequence of operations with minimization of the costs for equipment reconfiguration in the process of the en-terprise’s planned task execution.The developed methodology provides formation and systematic analysis of basic factors, such as the production of the required quantity of certain products.Developed the model adapted to modern production conditions, which in-cludes solving issues related to the optimal route choice, creation of cost-effective supply modes, finding minimal equipment downtime, pre-optimization of the exist-ing transport network, production of the required quantity of products with mini-mal costs.By analyzing the results obtained at each step of the specified problem so-lving for the purpose of further optimization, the proposed mathematical model can be implemented in the manufacturing process of any enterprise.  Such modelSuch model allows complex optimization of the enterprise processes as well as to achieve the set goals by adjusting the existing transport network.